2023
DOI: 10.1021/acs.iecr.3c00500
|View full text |Cite
|
Sign up to set email alerts
|

Crucial Role of Surface FeOx Components on Supported Fe-Based Nanocatalysts for CO2 Hydrogenation to Light Olefins

Abstract: Currently, Fe-based catalysts show excellent catalytic performance in the hydrogenation of CO 2 to produce light olefins. Despite numerous studies, the identification of the role of catalytically active components over Fe-based catalysts for CO 2 hydrogenation is not quite clear. In this work, a series of ZrO 2supported cobalt-doped Fe-based catalysts were fabricated by a microliquid film reactor-assisted coprecipitation method. It was demonstrated that appropriately strong interactions between Fecontaining sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 68 publications
0
1
0
Order By: Relevance
“…In previous studies on the CO 2 hydrogenation to olefins, supported iron catalysts have been widely investigated. For example, compared to the tetragonal ZrO 2 support, the high-surface-area monoclinic ZrO 2 support improved the Fe dispersion, as well as the Fe–ZrO 2 charge transfer induced by oxygen vacancies (O v ), thus favoring the generation of the χ-Fe 5 C 2 phase, contributing to the production of light olefins . Recently, through investigating the transformation of iron-containing phases in Fe-based catalysts during activation and reaction, our group revealed the crucial role of Fe 3 O 4 species having numerous oxygen vacancies on the activity and selectivity toward light olefins during CO 2 hydrogenation . Additionally, Shaikhutdinov et al reported that nanometer-sized Fe particles underwent strong interaction with planar oxide supports (i.e., SiO 2 , Al 2 O 3 ) to form a core (metal-rich)–shell (oxide-rich) structure during CO 2 hydrogenation, catalyzing the formation of CO and CH 4 as main products, as well as a small amount of C 2+ products with the low selectivity of 6–7%.…”
Section: Introductionmentioning
confidence: 99%
“…In previous studies on the CO 2 hydrogenation to olefins, supported iron catalysts have been widely investigated. For example, compared to the tetragonal ZrO 2 support, the high-surface-area monoclinic ZrO 2 support improved the Fe dispersion, as well as the Fe–ZrO 2 charge transfer induced by oxygen vacancies (O v ), thus favoring the generation of the χ-Fe 5 C 2 phase, contributing to the production of light olefins . Recently, through investigating the transformation of iron-containing phases in Fe-based catalysts during activation and reaction, our group revealed the crucial role of Fe 3 O 4 species having numerous oxygen vacancies on the activity and selectivity toward light olefins during CO 2 hydrogenation . Additionally, Shaikhutdinov et al reported that nanometer-sized Fe particles underwent strong interaction with planar oxide supports (i.e., SiO 2 , Al 2 O 3 ) to form a core (metal-rich)–shell (oxide-rich) structure during CO 2 hydrogenation, catalyzing the formation of CO and CH 4 as main products, as well as a small amount of C 2+ products with the low selectivity of 6–7%.…”
Section: Introductionmentioning
confidence: 99%